Strategies to manage electronic waste approaches: an overview in east Asia - Al-Rahmi, Waleed; Al-Rahmi, Norma; Ali, Akhtar; Yahaya, Noraffandy; Saleh, Muneer; Al-Maatouk, Qusay (International Journal of Engineering and Technology, 2018)
The issue of e-waste is becoming an increasingly threatening problem as it contains many toxic materials that can severely harm both human beings and the environment. This problem is expected to worsen if not serious efforts are taken to manage this e-waste. The current research introduced the best strategies and techniques with managerial efforts taken in this regard to deal with the e-waste in East Asia countries. Countries have been using a variety of techniques to deal with this problem namely: Life Cycle Assessment (LCA), Multi Criteria Analysis (MCA), Material Flow Analysis (MFA), and Extended Producer Responsibility (EPR). Therefore, these strategies are prosed to work to-gether to insure the best results in dealing with this problem. Moreover, this research involves a systematic and organized review of 308 research articles regarding electronic waste from 2000 to 2017. An analysis of studies dedicated to manage e-waste in East Asia countries was carried out on the basis of certain dimensions, namely, year of publication, journal, country, and subject area. Based on the obtained findings, the most of studies are from environmental science, chemistry, engineering, medicine and an energy area in the rate of (33.8%), (12.3%), (8.8%), (8.4%) and (5.8%) respectively. Furthermore, the findings have shown an increasing trend over recent years from 2010-2017.